Heat Transfer, Volume 3 2004
DOI: 10.1115/imece2004-59463
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Natural Convection in a Square Cavity Heated From Below

Abstract: This paper presents numerical results for two-dimensional steady-state natural convection in a square cavity. The upper and lower walls are kept at different constant temperatures, whereas the lateral walls have certain thickness and thermal conductivity and are externally insulated. Under these conditions we deal with a conjugate natural convection problem in which the heat conduction in the lateral walls is coupled with the internal convection. The continuity, momentum and energy equations were solved by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As seen, the passive area in which heat in circulated are also expanded. Figure 4 shows streamlines (on the left), isotherms (on the middle) and heatlines (on the right) at different thicknesses of partition for k ¼ 10 and Ra ¼ 10 5 . In this case, the thin part is taken as fixed but the thickness of the bottom part is changed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen, the passive area in which heat in circulated are also expanded. Figure 4 shows streamlines (on the left), isotherms (on the middle) and heatlines (on the right) at different thicknesses of partition for k ¼ 10 and Ra ¼ 10 5 . In this case, the thin part is taken as fixed but the thickness of the bottom part is changed.…”
Section: Resultsmentioning
confidence: 99%
“…Validation of the present code was performed by considering two different studies from the available literature by Kaminski and Prakash [1] and Sanchez et al [5]. In their work, the cavity is filled with a single viscous fluid and bounded by single or double walls with finite length and different thermal conductivity.…”
Section: Validation Of Numerical Codementioning
confidence: 99%
See 1 more Smart Citation
“…Validation of the present code was performed by two different studies from available literature as Kaminski and Prakash [19] and Sanchez et al [20]. In their case, the cavity is filled with single viscous fluid and bounded by single or double walls with finite length and thermal conductivity.…”
Section: Validation Of Numerical Codementioning
confidence: 99%
“…They indicated that inclination angle has a strong influence on heat transfer. Other studies can be found on natural convection in enclosures with single or multiple partitions in literature [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%